Transcriptomic analysis of mRNA expression and alternative splicing during mouse sex determination. (15th December 2018) - Zhao, Liang; Wang, Chenwei; Lehman, Melanie L.; He, Mingyu; An, Jiyuan; Svingen, Terje; Spiller, Cassy M.; Ng, Ee Ting; Nelson, Colleen C.; Koopman, Peter
Abstract: Mammalian sex determination hinges on sexually dimorphic transcriptional programs in developing fetal gonads. A comprehensive view of these programs is crucial for understanding the normal development of fetal testes and ovaries and the etiology of human disorders of sex development (DSDs), many of which remain unexplained. Using strand-specific RNA-sequencing, we characterized the mouse fetal gonadal transcriptome from 10.5 to 13.5 days post coitum, a key time window in sex determination and gonad development. Our dataset benefits from a greater sensitivity, accuracy and dynamic range compared to microarray studies, allows global dynamics and sex-specificity of gene expression to be assessed, and provides a window to non-transcriptional events such as alternative splicing. Spliceomic analysis uncovered female-specific regulation of Lef1 splicing, which may contribute to the enhanced WNT signaling activity in XX gonads. We provide a user-friendly visualization tool for the complete transcriptomic and spliceomic dataset as a resource for the field. Highlights: Transcriptomic & spliceomic dataset for mouse sex determination and gonadogenesis. Co-expression cohorts identify new candidates for sex development and sex disorders. The role of splicing regulation in this system may have been underappreciated.